2018
DOI: 10.1159/000490039
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor 3 Deficiency Affects Liver Lipid Metabolism

Abstract: Background/Aims: Tff3 protein plays a well recognized role in the protection of gastrointestinal mucosa. The role of Tff3 in the metabolism is a new aspect of its function. Tff3 is one of the most affected liver genes in early diabetes and fatty liver rodent models. The aim of this study was to investigate the effect of Tff3 deficiency on lipid and carbohydrate metabolism and on markers of oxidative stress that accompanies metabolic deregulation. Methods: Specific markers of health status were determined in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…This finding is consistent with results from a former study where Guillén et al showed a decreased Tff3 gene expression in mice with a stronger extent of liver steatosis [18]. Our findings in the liver of mixed background Tff3 −/− mice on a normal diet show that fat vacuole formation was also affected [35]. Ultrastructural analysis of the liver tissues show no difference in a number of immunologically relevant cells, and no difference in the general morphology of mitochondria, hepatocyte cell bodies, cytoplasm or capillaries between Tm-treated Tff3 −/− mice and Wt control mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with results from a former study where Guillén et al showed a decreased Tff3 gene expression in mice with a stronger extent of liver steatosis [18]. Our findings in the liver of mixed background Tff3 −/− mice on a normal diet show that fat vacuole formation was also affected [35]. Ultrastructural analysis of the liver tissues show no difference in a number of immunologically relevant cells, and no difference in the general morphology of mitochondria, hepatocyte cell bodies, cytoplasm or capillaries between Tm-treated Tff3 −/− mice and Wt control mice.…”
Section: Discussionsupporting
confidence: 93%
“…Tff3 −/− Tm-treated mice have a slightly but significantly higher expression level of GPX1 (1.35 fold) relative to Wt Tm-treated mice (Figure 3B). Previous reports showed no significant difference in liver GPX1 expression between WT and Tff3 −/− mice of mixed background in control condition similar as in this new strain background [35]. GPX activity in NAFLD livers compared to control is significantly higher [36] and the severity of disease is correlated with the decreased activity of GPX [37].…”
Section: Discussionmentioning
confidence: 56%
“…Profiling of plasma fatty acids concentrations was done in the Radiation Chemistry and Dosimetry Laboratory, Division of Materials Chemistry, Ruđer Bošković Institute (IRB), Zagreb, Croatia, according to previously described protocol [ 21 ]. Total lipids were extracted from plasma and treated with 0.5 M KOH/MeOH (Merck, Germany) to induce formation of the fatty acid methyl esters (FAMEs).…”
Section: Methodsmentioning
confidence: 99%
“…Individual fatty acids were determined in plasma samples and expressed as relative percentages of FAME obtained from total lipid extract. The percentage of FAME (a relative amount of each fatty acid) was quantified by integrating the area under the peak and dividing the results by the total area for all fatty acids [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genetically modified mice are frequently used stroke models for studying the molecular pathophysiology of stroke [15,16,17,18]. The Tff3 −/− / C57BL/6N ( Tff3 ) knockout mice model represents a promising new model for studying vascular function, atherosclerotic lesions, and the synthesis of proinflammatory cytokines due to altered lipid metabolism [19,20]. The metabolites of arachidonic acid (AA) have a significant role in mediating vascular reactivity to various stimuli, affecting tissue perfusion and supply, and exerting proinflammatory or anti-inflammatory effects on vessels and other tissues [21].…”
Section: Introductionmentioning
confidence: 99%